PENGARUH METODE PEER TUTORING DAN METODE STAD TERHADAP KETERAMPILAN MENULIS CERPEN SISWA - Nur Ainun Sari; Sulastriningsih Djumingin; Ambo Dalle (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to compare the effect of Peer Tutoring method and STAD method on short story writing skills of XI UPT class students of SMA Negeri 11 Makassar. This research used quasi experimental design by using nonequivalent control group design. The population in this study were all students of class XI UPT SMA Negeri 11 Makassar. The data collection technique of this study with the results of writing short stories on the initial test before being given treatment and the final test after being given treatment. Data analysis techniques used in this study were analysed using two types of statistics, namely descriptive statistical analysis and inferential statistics. The results showed that based on the data analysis of the independent sample t test by comparing the tcount with the ttable, the tcount value was 0.564 and the ttable (α: 0.05; df = 58) was 2.002. Thus, tcount = 0.564 < ttable (α/2) = 2.002; then H0 is accepted which indicates that there is no significant difference in the comparison of the effect of Peer Tutoring method and STAD method on short story writing skills of class XI UPT students of SMA Negeri 11 Makassar.